A comparative study of flexible electrode design on the performance of flexible wearable electronics - Khan, Akib Abdullah; Ban, Seunghyeb; Yeo, Woon-Hong; Kim, Jong-Hoon (Frontiers in Nanotechnology, 2025)
Flexible wearable electronics are promising for continuous health monitoring, particularly in electromyography (EMG) applications. A critical factor in their performance is electrode design, which affects mechanical resilience and electrical stability. Here, this study develops multiple electrode geometries: open-mesh, closed-mesh, and island-bridge, fabricated from gold-coated polyimide substrates to offer the best performance in EMG detection. Under standardized bending and stretching tests, the island-bridge design shows the lowest resistance variation (±1.61%), while the closed-mesh design provides balanced performance across various strains. EMG tests indicate that the closed-mesh electrodes deliver the highest signal-to-noise ratios (up to 14.83 dB) with minimal motion artifacts. Although the open-mesh design is flexible, it has lower electrical stability. In summary, the closed-mesh performs best overall, the open-mesh is better for handling motion artifacts, and the island-bridge is ideal for areas with minimal movement.